GE_GERICHTE P/21696/2016 vom 15. Dezember 2020 - GE Cour de justice (2020)
INFRACTIONS CONTRE LES DEVOIRS DE FONCTION;FAUX DANS LES CERTIFICATS;HOMICIDE;NÉGLIGENCE;MÉDECIN;MOYEN DE PREUVE;RÉCUSATION;INDEMNITÉ(EN GÉNÉRAL) | CPP.319; CPP.56; CPP.433; CPP.436; CPP.56; CP.251; CP.318; CP.117; CP.12